Long Noncoding RNA HAGLROS Promotes the Malignant Progression of Bladder Cancer by Regulating the miR-330-5p/SPRR1B Axis - Xiao, Shiwei; Zuo, Yigang; Li, Yanan; Huang, Yinglong; Fu, Shi; Yuan, Dongbo; Qiao, Xuhua; Wang, Haifeng; Wang, Jiansong (Frontiers in Oncology, 2022)
Bladder cancer (BC) is the most common genitourinary malignancy worldwide, and its aetiology and pathogenesis remain unclear. Accumulating evidence has shown that HAGLROS is closely related to the occurrence and progression of various cancers. However, the biological functions and underlying mechanisms of HAGLROS in BC remain unknown. In the present study, the expression of HAGLROS in BC was determined by public dataset analysis, transcriptome sequencing analysis, qRT–PCR and ISH assays. Gain- or loss-of-function assays were performed to study the biological roles of HAGLROS in BC cells and nude mouse xenograft model. Bioinformatic analysis, qRT–PCR, western blot, immunohistochemistry, FISH assays, subcellular fractionation assays and luciferase reporter assays were performed to explore the underlying regulatory mechanisms of HAGLROS in BC. Here, we found that HAGLROS expression is significantly upregulated in BC tissues and cells, and elevated HAGLROS expression was related to higher pathologic grade and advanced clinical stage, which is significant for BC diagnosis. HAGLROS can enhance the growth and metastasis of BC in vitro and in vivo. Furthermore, miR-330-5p downregulation reversed the BC cells proliferation, migration and invasion inhibited by silencing HAGLROS. SPRR1B silencing restored the malignant phenotype of BC cells promoted by miR-330-3p inhibitor. Mechanistically, we found that HAGLROS functions as a microRNA sponge to positively regulate SPRR1B expression by sponging miR-330-5p. Together, these results demonstrate that HAGLROS plays an oncogenic role and may serve as a potential biomarker for the diagnosis and treatment of BC.